Norman Fairclough’s Critical Discourse Analysis: Discourse of Married Life in the Film Pasutri Gaje - Hayiz Historia Adhi Pratama; Achmad Kanzulfikar; Fajar Aditiya Nugraha (LPPM Stikosa - AWS, 2025)
Marriage-themed films are a genre that not only depict harmonious and romantic married life but also reflect power relations and socio-cultural dynamics within a society. This study uses a qualitative approach with Norman Fairclough's critical discourse analysis method. The results show that the film Pasutri Gaje perpetuates and disrupts existing discourses regarding marriage in Indonesia. The discourses it attempts to perpetuate are the underprivileged status of civil servants and the social pressures that arise from the surrounding environment to have children. Both of these discourses are currently close to the reality of Indonesian society. Meanwhile, the discourse being disrupted in this film concerns fertility issues, which can also be caused by the desire to have children, including men who are portrayed as masculine. This is because fertility issues in Indonesia are more detrimental to women. The contribution of this study is that financial issues are the root of problems in married life. Therefore, this research is expected to provide insight for the government in reforming the welfare system for civil servants.